Digitalisasi Multi-Channel Sebagai Upaya Pengembangan UMKM Tenun Endek Bali - Antara, Made Ermawan Yoga; Martini, Ida Ayu Oka (LPPM Universitas HKBP Nommensen, 2024)
This Community Service activity was carried out at an SME which is engaged in the production of Balinese endek woven cloth, namely Tenun Tinizhop. Since its founding in 2018, Tenun Tinizhop has played a role in efforts to preserve local Balinese cultural wisdom through authentic Balinese woven fabrics produced using looms, not machines. The aim of this community service activity is to increase the promotion of woven fabrics by encouraging innovation through information technology, namely a multi-channel strategy. Implementing a multi-channel strategy can increase marketing promotions and sales of endek weaving products so that the endek weaving business will experience an increase and sustainable business goals can be achieved.